DESAIN PASAR JUNGKE KABUPATEN KARANGANYAR - TRISTIANTO, ANDI (Pendidikan Teknik Bangunan, 2013)
The purpose of the study was (1)Planning and designing Jungke Market becomes attractive, tradisional markets and reflects the local wisdom. (2)Planning and designing a notice Jungke Markets smooth circulation of people and goods. (3)Planning and design of traditional markets stall attention in structuring, arrangement an structuring los supporting facilities, creating traditional market regularly and properly classifiable.  The Study used a type of qualitative research. The research strategy used is description analysis. Data collected in this study is primary data obtained from the observation of the research object Jungke Market of Karanganyar which is one of the largest traditional market in the district of Karanganyar. Secondary data files or documents obtained from the Market Service of Karanganyar and Business Jungke. Tech data collection used was purposive sampling. The results of this study show that: (1)Market Desaign Jungke interesting and reflects local wisdom reflected: (a)The roof canopy which adopts the verandah roof Astana Giri Bangun Matesih. (b)The form of terraces which reflect colonial architecture adopting the form of the main building Tasikmadu Karanganyar Sugar Factory. (c)Form los reflects trading in the spot market atmosphere of traditional wisdom. (2)Design circulation Jungke Market with clear directions grid pattern support, effectiveness and ease of access space between the part of spece. (3)Design and los market stall grouping Jungke using a grid pattern makes the grouping of each function, type and character of any merchandise and types trading. (4)Design utility that prioritizes health and hygiene market reflected: (a)The drainage system using closed lines more visible neat and cleane. (b)Circulation network utility to use as the vertical circulation shaft will make easier to repair. (c)Waste management system with the use of waste as vertical circulation shaft will facilitate the distribution of garbage. (d)In addition, the separation between the organic and inorganic waste will be easier to recycle.  Keywords: Attractive design of Jungke Market, proper circulation, grouping of the clear, hygiene and good health.